Effects of drug-induced hepatotoxicity on vitellogenesis in the fathead minnow (Pimephales promelas) - Keding, Logan T. (My University, 2019)
The vitellogenin (VTG) assay is a test used to identify estrogen axis endocrine disruptors (EDs) in fish species. The VTG assay has been seemingly successful, though there are inherent limitations yet to be addressed. Since vitellogenin is produced in the liver, damage to the liver may inhibit vitellogenesis in the absence of any endocrine disruption. The goal of this project was to better understand the impact of liver toxicity on fathead minnow vitellogenin production. Adult female fathead minnows were exposed to a water- only control (n=56), vehicle control (0.1% ethanol (v/v); n=91), simvastatin (n=58) or simvastatin with acetaminophen (n=120) via flow-through water exposure. In a separate experiment, an estrone challenge (100 ng/L) was used to determine whether exposure rescued impacts on vitellogenin production due to liver damage. After 1, 3, 5, 6, or 9 days of exposure, VTG concentrations were measured with respect to indicators of liver toxicity (hepatosomatic index and histopathology). Impacts on liver damage were compared with VTG to determine whether this damage influences vitellogenesis. Preliminary findings suggest damage following 6 days of exposure may manifest in elevated VTG levels up to 3 days later. Furthermore, vitellogenesis may be a compensation mechanism for fat accumulation in the liver.
Keywords: Hepatotoxicology; Oogenesis; Fathead minnow; Biology